Spliceosomal small nuclear RNA genes in 11 insect genomes. - Mount, S.M.; Gotea, V.; Lin, C.F.; Hernandez, K.; Makalowski, W. (RNA (New York, N.Y.), 2007)
The removal of introns from the primary transcripts of protein-coding genes is accomplished by the spliceosome, a large macromolecular complex of which small nuclear RNAs (snRNAs) are crucial components. Following the recent sequencing of the honeybee (Apis mellifera) genome, we used various computational methods, ranging from sequence similarity search to RNA secondary structure prediction, to search for putative snRNA genes (including their promoters) and to examine their pattern of conservation among 11 available insect genomes (A. mellifera, Tribolium castaneum, Bombyx mori, Anopheles gambiae, Aedes aegypti, and six Drosophila species). We identified candidates for all nine spliceosomal snRNA genes in all the analyzed genomes. All the species contain a similar number of snRNA genes, with the exception of A. aegypti, whose genome contains more U1, U2, and U5 genes, and A. mellifera, whose genome contains fewer U2 and U5 genes. We found that snRNA genes are generally more closely related to homologs within the same genus than to those in other genera. Promoter regions for all spliceosomal snRNA genes within each insect species share similar sequence motifs that are likely to correspond to the PSEA (proximal sequence element A), the binding site for snRNA activating protein complex, but these promoter elements vary in sequence among the five insect families surveyed here. In contrast to the other insect species investigated, Dipteran genomes are characterized by a rapid evolution (or loss) of components of the U12 spliceosome and a striking loss of U12-type introns.